Revisiting the Meaning of Development: A Multidimensional Taxonomy of Developing Countries. - Tezanos Vázquez, Sergio; Sumner, Andy (Journal of Development Studies, 2013)
Many have challenged the use of income per capita as the primary proxy for measuring development since Seers’s seminal works. This article continues this tradition with a more recent twist. We use cluster analysis to build a multidimensional taxonomy of developing countries using a set of indicators covering four conceptual frames on ‘development’. The value-added of the article is not to suggest that our classification is the end in itself, but – more modestly – to demonstrate that more work on taxonomies is required in light of the weakness of classifications based solely on income and the changing distribution of global poverty.